Pengaruh Kreasi Dan Inovasi Terhadap Peningkatan Pendapatan Usaha Mikro Kecil Menengah - Ishak Ishak (Ecobuss, 2022)
The research was conducted with the aim of analyzing and explaining the effect of creation and innovation on increasing the income of micro, small and medium enterprises. The research was conducted on MSMEs in Rembang Market - Pasuruan. Data were collected through observation, document analysis, and distributing questionnaires. The method of data analysis was carried out with a descriptive quantitative method with analysis using SPSS. The results show that first, the variables have a simultaneous effect on creativity and innovation on entrepreneurship. Second, the creativity variable has a partial effect on entrepreneurship. Third, the innovation variable has a partial effect on entrepreneurship. Fourth, the most influential innovation variable on entrepreneurship.